Effectiveness of Training Session in Improvement of Insulin Administration Technique in Diabetic Patients - Khalid, Abdul; Rafique, Rubina; Arshed, Ali; Nazir, Munazza; Ahmed, Ashfaq (International Journal of Pathology, 2018)
Objective: To evaluate the effectiveness of training session in improvement of insulin administration technique in diabetic patients.Methods: The cross- sectional analytical study was conducted in Department of medicine Abbas Institute of Medical Sciences Muzaffarabad from April 2017 to August 2017.100 patients were recruited for studyinterviewed regarding their knowledge and practices of insulin injection. Patients with incorrect injection technique were observed during administration of insulin injection. Education session was conducted and patients were given feedback about their mistakes. The injection technique was re-observed after the education session and follow up with same set of questions was made in same session.Results: The injection technique was incorrect in 26%, partially correct in 54% and correct in 18% of patients before education session. After the education session injection technique was correct in 92% of patients. It was partially correct in 8% while no patient had incorrect technique. These results were statistically significant (p< 0.001) when compared with one sample t-test.Conclusion: Few minutes of teaching and guidance by health care professionals brings remarkable change regarding patient’s awareness for correct application of insulin injection technique.